Nutritional, Therapeutic and Functional Applications of Sorghum: A Comprehensive Review - Sinha, Nupur; Anju Thomas (Jurnal Kebidanan Manna, 2024)
Sorghum is a valuable source of bioactive compounds with a variety of health benefits. Its bioactive components include phenolic acids, flavonoids, tannins, and dietary fiber, all of which contribute to its functional food properties. Some of the key bioactive compounds in sorghum and their health benefits: Sorghum contains high levels of phenolic acids, such as caffeic, p-coumaric, and ferulic acids. These compounds act as powerful antioxidants, helping to reduce oxidative stress in the body, which is linked to inflammation, cancer, and cardiovascular disease. Sorghum is particularly rich in flavonoids such as luteolin, apigenin, and their derivatives. These compounds are known for their anti-inflammatory, anticancer, and neuroprotective properties that help improve cardiovascular health by reducing the risk of plaque formation in the arteries. Certain varieties of sorghum, especially the pigmented ones, contain condensed tannins also known as proanthocyanidins. Sorghum is rich in both soluble and insoluble fiber. The dietary fiber in sorghum aids digestion, supports gut microbiome health, and contributes to better blood glucose control. Regular fiber intake may reduce the risk of colorectal cancer and aid in weight management. These long-chain alcohols are thought to help lower LDL cholesterol levels, which is beneficial for cardiovascular health. The polycosanols in sorghum have been found to improve lipid metabolism and may aid in weight management. Specific phytochemicals with antioxidant properties, such as phytic acid, polyphenols, tannins, and sterols, have been shown to reduce the incidence of chronic diseases and play a role beyond just food.